Marketing Strategy of Coffee Shop Case Study: Rasa Kopi Bandung - Faiz, Muhammad; Putra, Bintang; Raihan, Muhammad; Riezki, Dian; Ariatin, Adrian (Cahaya Ilmu Bangsa, 2025)
In an era of rapid development, the coffee industry has also advanced significantly, leading to intense competition in the coffee market. This growth in trends has expanded the popularity of coffee, making it highly sought after. This phenomenon has made consumer preferences crucial for increasing purchasing interest, especially when employing